Perbandingan Metode Single Exponential Smoothing, Double Exponential Smoothing, dan Triple Exponential Smoothing dalam Analisis Realisasi APBD Kota Medan - Riri Syafitri Lubis; Dinda Renata Cecilia; Sintia Agustina Siregar; Fuja Nauli Pasaribu; Ahmad Sugarda (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This research compares three forecasting methods, namely Single Exponential Smoothing (SES), Double Exponential Smoothing (DES), and Triple Exponential Smoothing (TES), in analyzing the realization of the Medan City Regional Budget (APBD) for the 2019-2024 period. This study aims to find the most accurate method in forecasting the budget, so that it can help optimize the use of APBD by local governments. The APBD realization data was analyzed using Minitab software, and the accuracy of the method was measured based on Mean Absolute Percentage Error (MAPE). The results showed that TES has the smallest MAPE value of 0.12%, compared to SES (12%) and DES (14%). Thus, TES is the best method to predict the budget realization in the following year, producing a forecasting value of 5,500.86 million rupiah. This research is expected to support the government in making more precise and efficient budget decisions.